Alman Z-Score Analysis For Predicting Bankruptcy In Pharmaceutical Companies Listed On The Indonesia Stock Exchange - Jadongan Sijabat; Sertika Elvi Nanda (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
This study aims to determine and analyze the risk of bankruptcy of pharmaceutical companies on the Indonesia Stock Exchange based on the Altman Z-Score method. This research uses a type of quantitative descriptive research using secondary data sources. The data collection technique used is a documentation technique in the form of financial reports comprising ten companies for the 2017-2021 period. The method used to analyze bankruptcy risk is the revised Altman method. Where the ratio used is in the form of company financial ratios based on Altman Z Score, namely working capital to total assets (T1), retained earnings to total assets (T2), earnings before interest and taxes to total assets (T3), market value of equity to book value of liability (T4), and sales to total assets (T5). The Altman method in this study can be calculated using the following formula: Z = 0,717 T1 + 0,847 T2 + 3,107 T3 + 0,420 T4 + 0,998 T5. The results of this study indicate that three companies are at risk of bankruptcy or are in a distress zone, namely PT Indofarma (Persero) Tbk (INAF), PT Kimia Farma Tbk (KAEF), and PT Pharos Tbk (PEHA). Besides that, there are three companies in the grey area zone, and four companies in a safe condition. For the company to avoid bankruptcy risk, the company can improve the company's financial performance by optimizing the company's assets, increasing sales volume, and reducing production costs.